High School Athletes' Reports of Confirmation as a Function of Starting Status and Leader–Member Exchange. (August 2019) - Cranmer, Gregory A.; Arnson, Emily; Moore, Andrew; Scott, Alexander; Peed, Joshua
Previous research indicates that athletes report receiving disparate levels of confirmation, which is consequential given the psychological, emotional, and cognitive benefits of being confirmed. This article explains head coaches' use of confirmation, which is comprised of accepting and challenging communication, as a function of athletes' roles and leader–member exchange (LMX). Data obtained from 197 high school athletes—representing 17 sports and from 16 states—substantiated that starters receive more recognition and acknowledgement of their efforts and accomplishments (i.e., acceptance) but are not more likely to receive communication that seeks the refinement of their potential (i.e., challenge). LMX with head coaches, however, accounted for much larger portions of variance in reports of receiving confirmation, with in-group relationships being predictive of greater amounts of confirmation. These results indicate that confirmation is received as a function of the roles of athletes and their interpersonal relationships with coaches. Such findings provide mechanisms to explain disparate experiences of confirmation and connect two theoretical bodies of literature in a manner that intersects the organizational and interpersonal processes of coaching.